High CCL2 Levels Detected in CSF of Patients with Pediatric Pseudotumor Cerebri Syndrome - Jacob Genizi; Lotan Berger; Muhammad Mahajnah; Yulia Shlonsky; Orit Golan-Shany; Azriel Romem; Ayelet Halevy; Keren Nathan; Rajech Sharkia; Abdelnaser Zalan; Aharon Kessel; Rony Cohen (MDPI AG, 2023)
Pseudotumor cerebri (PTC) is a disorder characterized by increased intracranial pressure in the absence of a structural lesion or other identifiable cause. Cytokines, which are involved in the regulation of immune responses and inflammation, have been implicated in the pathogenesis of PTC. In a prospective, cross-sectional study at three centers in Israel, we analyzed cerebrospinal fluid (CSF) samples from 60 children aged 0.5-18 years, including 43 children with a definitive diagnosis of PTC and a control group of 17 children. Levels of IL-4, IL-10, IL-17, CCL2, CCL7, CCL8, CCL13, BDNF, and IFN-γ were measured using ELISA kits. Levels of CCL2 were significantly higher in the PTC group compared to the control group (p < 0.05), with no other significant differences in the measured cytokines between the two groups. The groups did not differ significantly in clinical presentation, imaging, treatment, or ophthalmic findings. Our findings provide preliminary evidence that CCL2 may be involved in the pathogenesis of PTC and may serve a potential target for therapy in PTC.